Model Pelayanan Sistem Kependudukan dalam Meningkatkan Kualitas Pelayanan Kependudukan - Taufik Hidayat; Ahmad Gani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In era of digital technology 4.0, it is developing like a storm, so the use of technology in this digital era needs to be utilized properly. The main problem of daily life is not being able to manage data well from various fields such as citizen data. Key issues in managing citizen data from the lowest level. Factors that create economic, social, cultural and security barriers can actually contribute if embedded data management is properly implemented. The most important thing is data processing, population data collection, one of which is influenced by population movement and population income processes, and Bigdata is needed to accommodate these data. The results of the research conducted that the response from the community is positive so that further development is needed in its application so that it can provide good services. Suggestions for further research to integrate other services so that the current community needs can be accommodated properly so that the future is even better.